2012
DOI: 10.3354/meps09561
|View full text |Cite
|
Sign up to set email alerts
|

Seabird predation on Arctic cod during summer in the Canadian Arctic

Abstract: Seabirds feed heavily on Arctic cod Boreogadus saida during the summer in the Canadian Arctic but little is known of the interactions among birds while foraging and the factors that drive feeding behaviour. The objective of this study was to describe the relationship between seabirds and Arctic cod in a productive feeding area distant from breeding colonies. Transect surveys were completed using standardized count protocols to determine the density of seabirds in Allen Bay, Cornwallis Island, Nunavut. Shore-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…However, smaller and sparsely dispersed non-schooling Arctic cod appear to be a significant source of food, particularly for ringed seals. During several months of observations in Allen Bay (Matley et al 2012), ringed seals did not forage on schools of Arctic cod near the surface, yet belugas and harp seals often did*an observation also noted by Bradstreet et al (1986). Interestingly, the mean length of net-captured Arctic cod from schools in Allen Bay was 187.0 mm (Crawford & Jorgenson 1996), while non-schooling adults in Resolute Bay were 163.5 mm (Hop et al 1997).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…However, smaller and sparsely dispersed non-schooling Arctic cod appear to be a significant source of food, particularly for ringed seals. During several months of observations in Allen Bay (Matley et al 2012), ringed seals did not forage on schools of Arctic cod near the surface, yet belugas and harp seals often did*an observation also noted by Bradstreet et al (1986). Interestingly, the mean length of net-captured Arctic cod from schools in Allen Bay was 187.0 mm (Crawford & Jorgenson 1996), while non-schooling adults in Resolute Bay were 163.5 mm (Hop et al 1997).…”
Section: Discussionmentioning
confidence: 51%
“…This is not surprising considering that Arctic cod aggregated in abundant schools in Allen Bay during the sampling period (see Matley et al 2012) and are known to be heavily exploited by predators in this area (Hobson & Welch 1992;Hop et al 1997). This research also showed differences in ringed seal feeding patterns among individuals and compared to the toothed whales based on multiple sampling techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Sea ice distribution is another factor known to influence the abundance and distribution of seabirds [ Hunt , ; Stirling , ]. Ice algae found under the sea ice forms the foundation of the Arctic food web [ Horner , ], linking the organisms found on the undersurface of sea ice [ Horner , ] to the higher trophic level organisms such as amphipods and Arctic cod [ Bradstreet and Cross , ; Gradinger and Bluhm , ], which are prey for many species of Arctic seabirds [ Bradstreet , ; Bradstreet and Cross , ; Welch et al ., ; Matley et al ., ]. Diving piscivores, such as thick‐billed murres, are often associated with offshore ice edges and coastal landfast ice edges [ Bradstreet , ], which are also critical in the breeding distribution and timing of this species in the high Arctic [ Laidre et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Local wind conditions are known to affect the presence of prey species (e.g. [23] ) and the ability of seabirds to capture prey [24] . Scientists are now realizing that a change in wind regimes can have important consequences for seabird foraging conditions and consequently their life history [25] .…”
Section: Introductionmentioning
confidence: 99%